Annual Plan 1995-96 Government of India Planning Commission - Planning Commission (Planning Commission, 1995)
Central Government Budget (Per cent of GDP) Central Government Revenue Receipts (As percent of GDP) Public Sector Plan Outlay/Expenditure for the Eighth Five Year Plan and Annual Plans 1992 Financing of State Sector Financing of Central Sector Plan in the Annual Plan (1992-96) Public Sector Plan Outlay Plan Outlay/Expenditure By Heads of Development - Central Sector Budgetary Support by Heeds of Development during Eighth Plan end Annual Plans (1992-96)- Centre Sectoral Growth in Gross Domestic Product (Annual Growth at 1980-81 Prices) Annual Growth Rates of Indices of Industrial Production (Base 1980-81=100)
Government of India Planning Commission